2004
DOI: 10.1007/s00125-004-1572-7
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative treatment prevents activation of death-receptor- and mitochondrion-dependent apoptosis in the hearts of diabetic rats

Abstract: The present study indicates that reactive oxygen species induced by high glucose are involved in both death-receptor- and mitochondrion-dependent apoptosis in the heart in vivo. It also suggests that antioxidants may be a therapeutic option for preventing cardiovascular damage in diabetes mellitus in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
57
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 33 publications
6
57
0
Order By: Relevance
“…The significant correlations of Fas-L and TNF-α with e'/a' ratio and ventricular global peak systolic strain in diabetic patients may demonstrate that apoptosis plays a role in the pathogenesis of DCM. The ability of ALA to lower Fas-L level in our study is consistent with Bojunga et al who reported that ALA decreased Fas-L gene expression in the hearts of diabetic animals and prevented the activation of death receptor signaling [41].…”
Section: Discussionsupporting
confidence: 93%
“…The significant correlations of Fas-L and TNF-α with e'/a' ratio and ventricular global peak systolic strain in diabetic patients may demonstrate that apoptosis plays a role in the pathogenesis of DCM. The ability of ALA to lower Fas-L level in our study is consistent with Bojunga et al who reported that ALA decreased Fas-L gene expression in the hearts of diabetic animals and prevented the activation of death receptor signaling [41].…”
Section: Discussionsupporting
confidence: 93%
“…Antioxidative treatment with ALA significantly suppressed apoptosis, suggesting that antioxidants may be a therapeutic option for preventing cardiovascular damage in DM in humans (Bojunga et al 2004). In accordance with these findings, we used STB as a potent antioxidant agent to reduce the ischemia-reperfusion injury of isolated diabetic hearts.…”
Section: Discussionsupporting
confidence: 61%
“…It is interesting to note that the alteration in mitochondrial function in vitro and in vivo has been shown to correlate with the levels of activation of AKT and BcL-2 family protein (23, 40 -42). A decrease in BcL-2 family members has been suggested to contribute to apoptosis and the translocation of cytochrome c from the mitochondria to cytosol (23,41,43). Activation of AKT has been shown to augment ATP synthesis (44), promote association of hexokinase with the VDAC channel and, in so doing, promote VDAC closure, thus blocking release of cytochrome c (45).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in ROS contributes to degenerative changes in mitochondrial function (13) and membrane depolarization (21). Mitochondrial ROS production associated with hyperglycemia is increased because of the lack of antioxidants, thus restoration of antioxidant levels is beneficial in decreasing mitochondrial membrane dysfunction (22,23). Abnormalities in mitochondrial transport, either through a decrease or an increase in one of the carriers, have been shown to cause an increase in superoxide anion (O 2 Ϫ ) production (24).…”
mentioning
confidence: 99%